1982
DOI: 10.1063/1.442804
|View full text |Cite
|
Sign up to set email alerts
|

The rotational spectrum and molecular structure of the ethylene–HF complex

Abstract: The microwave spectrum of the ethylene–HF complex in the ground vibrational state has been assigned using a Fourier transform microwave spectrometer, employing a Fabry–Perot cavity and a pulsed supersonic nozzle as a molecular source. Ethylene–HF is nonplanar, with the axis of the HF subunit oriented perpendicular to the plane of the ethylene molecule, and bisecting the carbon–carbon double bond. A hydrogen bond is formed between the HF proton and the π-electron density of ethylene. The spectroscopic constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(31 citation statements)
references
References 17 publications
0
30
0
1
Order By: Relevance
“…Rather, these species are potent oxidizers, and undergo direct oxidation reactions at room temperature with most reaction partners. However, theoretical efforts have been put forth to study complexes of these reactive halogens, and have predicted [19,20,80] substantial stability for complexes of C1F, if they could be isolated prior to further reaction. Consequently, we have examined a number of systems which employ C1F (or occasionally C12) as the Lewis acid.…”
Section: Intermediate Complexes Of Highly Reactive Reagentsmentioning
confidence: 99%
“…Rather, these species are potent oxidizers, and undergo direct oxidation reactions at room temperature with most reaction partners. However, theoretical efforts have been put forth to study complexes of these reactive halogens, and have predicted [19,20,80] substantial stability for complexes of C1F, if they could be isolated prior to further reaction. Consequently, we have examined a number of systems which employ C1F (or occasionally C12) as the Lewis acid.…”
Section: Intermediate Complexes Of Highly Reactive Reagentsmentioning
confidence: 99%
“…It has captured the interest of chemists for a long time and reports about its theory and experiment have been well represented [1−9] . It has been found that a lot of physical and chemical phenomena are closely related to the intermolecular weak interactions including hydrogen bond [10−12] , π-cation [13] , halogen bond [8,14,15] , lithium bond [9,16,17] , etc. Among these intermolecular interactions, hydrogen bond is the earliest and the most extensive one among such interactions studied, and lithium bond is an interesting interaction analogous to hydrogen bond [18] .…”
mentioning
confidence: 99%
“…It has captured the interest of chemists for a long time and reports about its theory and experiment have been well presented. [1][2][3][4][5][6][7][8][9] It has been found that a lot of physical and chemical phenomena are closely related to the intermolecular weak interactions including hydrogen bond, [10][11][12] π-cation, 13 halogen bond, 8,14,15 lithium bond, 9,16,17 etc. Among these intermolecular interactions studied, hydrogen bond is the earliest and the most extensive one, and lithium-bond is an interesting interaction analogous to hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%